TRANSFER OF PROPERTY IN CONTRACTS FOR THE INTERNATIONAL SALE OF MOVABLE CERTAIN - Parra Rivera, Rose Mary (2015)
Article research addresses the problem of how and when it is determined that the improvement of the transfer of ownership of the property determined in the international sales contract. For it is based on the description of the property transfer system in comparative law in the solutions given to the subject in several of the schemes belonging to the civil law family. A how various codes including our belonging to the Roman-Germanic system include the effects to recognize the contract of sale, since this regard there are two (02) positions: the first, which recognizes real effects (holding that contract is sufficient), and another that only recognizes obligational effects (which also requires the contract an additional act.). All this to seek to identify international business practice of these operations, the precise time it occurs the transfer of ownership of the right of ownership of certain property, leaving the domain field of the exporter-seller (former owner) and simultaneously entering the field of property of the importer-buyer (new owner), concluding that the time when improvement occurs when the property is ¨ given provision of the goods ¨ (fictitious delivery), which depend if the transaction is deal with the transport of goods or without it.